PENGARUH PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) TERHADAP PRODUKTIVITAS PEGAWAI PT PERTAMINA GEOTHERMAL ENERGY AREA LAHENDONG - Rantung, Rafael; Manueke, Selfy; Wollah, Meidy; Dua, Iyam L. (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2024)
Productivity is the relationship between output and input which in this case aims to realize an increase in the company's production. The purpose of this study is: to determine the effect of the application of standard operating procedures on the work productivity of employees of PT.Pertamina Geothermal Energy Area Lahendong. This type of research is quantitative research and this research method uses descriptive research methods, namely describing phenomena or problems that are happening to an object of research. In this study, samples were taken from one population using a questionnaire as a data collection tool. The population taken is all employees at PT Pertamina Geothermal Energy Area Lahendong with a total of 98 employees while the sample is 49 respondents. Meanwhile, the results of the research analysis show that the correlation coefficient R = 0.118 shows that Standard Operating Procedures have a very low relationship to employee work productivity at PT Pertamina Geothermal Energy Area Lahendong. The value of the coefficient of de-termination R square = 0.014% indicates that there is no significant effect on increasing employee work productivity at PT Pertamina Geothermal Energy Area Lahendong